Review paperEar involvement in systemic lupus erythematosus - Waszczykowska, Elżbieta; Pajor, Anna; Erkiert-Polguj, Anna; Maciaszczyk, Katarzyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Systemic lupus erythematosus is an autoimmune disease. There are many symptoms from different organs, and also ear involvement is examined. Sensorineural hearing loss and tinnitus are the most common symptoms of ear involvement in SLE. Literature data are presented.